Alpine Industrial Landscapes Towards a New Approach for Brownfield Redevelopment in Mountain Regions - Modica, Marcello (RaumFragen: Stadt - Region - Landschaft, 2022)
This Open Access book presents a pioneering research on brownfield redevelopment in mountain regions, and specifically in the European Alps. The origins and causes, the actual conditions as well as the future challenges and potentials of mountain brownfields are investigated from an interdisciplinary yet landscape-centered perspective. Through the reasoned combination of research-by-design methods and case-study analysis, the book explores the infrastructural relevance of these sites for the specific mountain territory, while advancing an innovative structuralist-systemic approach for their physical and functional transformation. The book includes, among others, a first transnational geo-mapping of Alpine brownfields, whose impressive outcomes in terms of site numbers and distribution can only confirm the urgency of this research.